New ductile laminate structure of Ti-alloy/Ti-based metallic glass composite with high specific strength. Issue 4 (April 2018) - Li, D.; Zhu, Z.W.; Wang, A.M.; Fu, H.M.; Li, H.; Zhang, H.W.; Zhang, H.F.
Abstract: Bulk laminate structure of Ti-alloy/Ti-based metallic glass composite (MGC) was prepared by melting a preform of alternate stack-up foils in the high vacuum atmosphere. The composite demonstrates a good combination of yield strength (∼1618 MPa), plasticity (∼4.3%) and specific fracture strength (384 × 10 3  N m kg −1 ) in compression. The maintained yield strength results from the unique microstructure composed of the Ti layer, the solution layer with gradient structure and the MGC layer. Such a multilayer structure effectively inhibits the propagation of shear band, leading to the enhanced plasticity. Those extraordinary properities suggest that combining ductile lamella with brittle metallic glass (MG) by such a lay-up method can be an effective way to improve mechanical properties of MG.